Moral And Aesthetic Education And Family Atmosphere In The Legacy Of Zakhiriddin Muhammad Babur (Open Academia: Journal of Scholarly Research, 2026)
This article provides a scientific and theoretical analysis of moral and aesthetic education and the role of family environment in the spiritual heritage of Zakhiriddin Muhammad Bobur. Particular attention is given to the ethical, aesthetic, and educational ideas reflected in his works, especially in Boburnoma, where issues of human morality, cultural refinement, and family upbringing are implicitly and explicitly addressed. The study examines Bobur’s views on the formation of a morally responsible and aesthetically developed personality within the family context. It highlights the family as a key social institution where moral values, aesthetic taste, and behavioral norms are initially shaped. The research also demonstrates that Bobur’s ideas are grounded in humanistic principles, emphasizing respect, harmony, emotional balance, and moral integrity within family relations. Furthermore, the article analyzes the relevance of Bobur’s moral-aesthetic concepts in the context of modern educational challenges, including the transformation of family values and the weakening of traditional cultural continuity. His ideas are interpreted as an important methodological basis for strengthening moral education and improving the quality of family upbringing.